Dynamic service arbitration for autonomic Internet of things - Ashraf, Qazi Mamoon; Habaebi, Mohamed Hadi; Islam, Md. Rafiqul (InterNetWorks Research Lab School of Computing, 2015)
Recent research on Internet of Things (IoT) has focused on the adaptation of the autonomic computing paradigm to make IoT self-sufficient. Service arbitration is one aspect which can greatly benefit from the adoption of the autonomic theory. Instead of allowing all deployed devices to be active, only a selected set of devices can be utilized to provide for a particular service. This paper motivates the need for a dynamic service arbitration scheme for this purpose. Such a method can supplement existing autonomic frameworks with the aim to minimize user intervention as well as imparting selfconfiguration in the system.